Peran Media Sosial: Employer Branding Terhadap Minat Kerja Mahasiswa Tingkat Akhir di Kalimantan Utara - Aswan Aswan; Deni Marsha; Erick Karunia; Shalahuddin Shalahuddin; Muh. Irfandy Azis; Suryaningsih Suryaningsih (Pusat Riset dan Inovasi Nasional, 2025)
In the competitive digital era, companies are required to build an image as an attractive workplace to capture the attention of young talent, especially generation Z who will enter the job market. This study aims to analyze the effect of employer branding on the interest in applying for jobs of final year students in North Kalimantan, and to examine the role of social media as a moderating variable in the relationship. The study used a quantitative approach with an explanatory design through a survey method of 350 students from two universities, with data analysis using Structural Equation Modeling-Partial Least Squares (SEM-PLS) techniques. Employer branding was measured based on five dimensions of organizational attractiveness, while job application interest and social media exposure were measured using a Likert scale. The results showed that employer branding has a positive and significant effect on job application interest (β = 0.506; p = 0.002), and social media also has a significant direct effect on job application interest (β = 0.573; p = 0.000). However, the moderating effect of social media on the relationship between employer branding and interest in applying was not statistically significant (β = -0.088; p = 0.969). The findings conclude that while social media is effective as a direct communication channel, its success in strengthening employer brand image depends on the quality of content and consistency of the organization's narrative. The implication of this study suggests that local companies should strengthen their employer branding strategy and utilize social media more purposefully and contextually to attract young talent in frontier regions.